PERSAMAAN NILAI PENDIDIKAN DALAM RITUS AGAMA HINDU: MENINJAU KESINAMBUNGAN NILAI-NILAI PENDIDIKAN DALAM RITUAL UPACARA KELAHIRAN, PERNIKAHAN, DAN KEMATIAN DALAM AGAMA HINDU: Indonesia - Miming Oktorianisarry; I Gede Dharman Gunawan; Tardi Edung (Guna Widya: Jurnal Pendidikan Hindu, 2024)
Equation of the Value of Education in Hindu Rites: Reviewing the Continuity of the Values of Education in the Rites of Birth, Marriage, and Death in the Hindu Religion is a Library Research. The aim of this study is to find the similarity of the values of education in the rituals of birth, marriage, and death in Hinduism. The journals that were reviewed came from various Hindu streams in Indonesia, Hindu Java, Kaharingan, and Bali. There are five journeys about birth ceremonies, five about marriages, and five about death. The results of this study found that the same values that exist in every ceremony or ritual in Hinduism are the value of philosophy education (Tatwa), which aims to teach people to understand the truth of life, pursue true science, and develop spiritually. Hindu Tatwa teaches us that life is a way to gain a deeper understanding of nature and ourselves. Tattwa also emphasizes principles such as honesty, self-awareness, love, and self-control. Ethical education values (Susila), or moral education in Hindu tradition, provide a solid foundation for society to develop good habits and morals. The best practice in carrying out this ceremony is based on the concept of the Tri Kaya Parisudha, which emphasizes the holiness, honesty, and faith in the life of Hyang Widhi. Based on the teachings of the Tri Kaya Parisudha, teaching good morals and ethics and good behavior in speaking, speaking, and acting is very important for family relationships. Through ritual education and ceremonies, individuals can learn about discipline, respect, spiritual awareness, communion, and purification. These values shape the individual's character and help them in everyday life. The researchers also found that some studies presented social and aesthetic values in some Hindu rituals, which highlighted social education, and good relationships between humans and the environment. It is evident from the way the merchandise is plotted according to Hindu teachings to produce a beautiful, clean, and fortunate offering.